The impact of allergen specific immunotherapy with house dust mite allergens on natural course of asthma in children - O. V. Trusova; Y. L. Mizernitskiy; V. I. Trofimov; A. V. Kamaev; N. B. Platonova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Objective. To assess the dynamics of bronchial asthma (BA) and allergic rhinitis (AR) caused by house dust mites (HDM) in children during 3 years of allergen specific immunotherapy (ASIT) with HDM allergens and 1 year after treatment cessation.Research methods. 50 patients completed an open, prospective, controlled 5-year study. 25 patients of the main group with BA and sensitization to HDM underwent a year of preliminary observation, 3 years of ASIT with HDM allergens, and 1 year of follow-up: 16 boys (64%), 9 girls (36%), 5 years to 13 years (8.3 [6.7; 11.5]) at inclusion. The control group of 25 patients, who did not receive ASIT, was selected as pairs copies. At inclusion, the concentration of periostin and thymic stromal lymphopoietin (TSLP) in blood serum and nasal material was determined in all patients. The dynamics BA and AR was assessed based on the total index of symptoms and medications for each year of observation.Results. During 3 years of treatment, a significant clinical effect of ASIT was formed, which persisted for 1 year of follow-up after the end of ASIT. At the end of the follow-up year, the overall index of symptoms and medications was 8.77 ± 1.06 points in the ASIT group and 22.01 ± 2.18 points in the control group (p=0.00001). The concentration of periostin before the start of treatment did not affect the effectiveness and features of the ASIT treatment course. A high serum TSLP concentration (>750 pg/ml) is characteristic of the subgroup with a higher incidence of adverse events associated with ASIT; the final effectiveness of ASIT does not depend on the concentration of this marker.Conclusion. ASIT with HDM sublingual drops is the method of first choice in the treatment of children with BA and AR, in cases where the role of HDM allergens in the genesis of the disease has been proven. A successful ASIT has a prolonged effect (at least 1 year of follow-up), which indicates the possibility of changing the natural course of asthma in children. The study of biomarkers does not allow us to predict the effectiveness of ASIT.